Steno type 1 risk engine and preclinical atherosclerosis in Mediterranean individuals with type 1 diabetes. Issue 7 (13th April 2020) - Viñals, C.; Conget, I.; Pané, A.; Boswell, L.; Perea, V.; Blanco, A. J.; Ruiz, S.; Giménez, M.; Vinagre, I.; Esmatjes, E.; Ortega, E.; Amor, A. J.
Abstract: Background and aims: Tools to detect type 1 diabetes (T1D) individuals at overt cardiovascular disease (CVD) risk are scarce. We aimed to assess the usefulness of the score 'Steno Type 1 Risk Engine' (Steno‐Risk) to identify T1D patients with advanced carotid atherosclerosis. Material and methods: T1D patients without CVD with at least one of the following were included: ≥40 years, diabetic nephropathy, or diabetes duration ≥10 years with ≥1 CVD risk factor. Intima‐media thickness (IMT) and plaque presence (IMT ≥1.5 mm) were assessed by standardized B‐mode ultrasonography. Steno‐Risk was used to estimate 10‐year risk (<10% low; 10%‐20% moderate; ≥20% high risk). Associations between Steno‐Risk and preclinical atherosclerosis were assessed after adjusting for other CVD risk factors. Results: We evaluated 302 patients (55% men, age 47.8 ± 9.8 years, T1D duration 26.3 ± 9.3 years). The prevalence of carotid plaque and ≥2 plaques were 36.4% and 19.2%, respectively; without sex differences. Age (57.4 ± 7.4 vs 37.1 ± 6.2 years), T1D duration (31.3 ± 10.4 vs 21.5 ± 7.1 years), hypertension (52.3% vs 6.3%), nephropathy (25.6% vs 5.1%) and retinopathy (53.5% vs 32.9%) were higher in high‐risk (n = 86) vs low‐risk participants (n = 79; P < .001 for all). Preclinical atherosclerosis (IMT and plaque) increased in parallel with Steno‐Risk ( P < .001). In logistic regression analysis, both age ≥40 years and Steno‐Risk ≥20% were associated with the presence of plaque (OR 4.22 [1.57‐11.36] and 3.79 [1.61‐6.80]; respectively), but only high Steno‐Risk remained independently associated with ≥2 plaques (OR 3.31 [1.61‐6.80]). Conclusion: Steno‐Risk is independently associated with preclinical atherosclerosis. Further studies are needed to ascertain its usefulness in this high‐risk population.